High-Quality Real-Time Stereo Using Adaptive Cost Aggregation and Dynamic Programming - Liang Wang; Miao Liao; Minglun Gong; Ruigang Yang; Nister, D. (3DPVT 2006 : Third International Symposium on 3D Data Processing, Visualization, and Transmission : June 14-16, 2006, University of North Carolina, Chapel Hill, USA, 2006)
We present a stereo algorithm that achieves high quality results while maintaining real-time performance. The key idea is simple: we introduce an adaptive aggregation step in a dynamic-programming (DP) stereo framework. The per-pixel matching cost is aggregated in the vertical direction only. Compared to traditional DP, our approach reduces the typical "streaking" artifacts without the penalty of blurry object boundaries. Evaluation using the benchmark Middlebury stereo database shows that our approach is among the best (ranked first in the new evaluation system) for DP-based approaches. The performance gain mainly comes from a computationally expensive weighting scheme based on color and distance proximity. We utilize the vector processing capability and parallelism in commodity graphics hardware to speed up this process over two orders of magnitude. Over 50 million disparity evaluations per second (MDE/s)1 are achieved in our current implementation.